Infant and child mortality in Andhra Pradesh - White, H (2003)
Most countries of the world are reducing infant and child mortality too slowly to meet the Millennium Development Goal (MDG) of a two-thirds reduction by 2015. Yet, some countries and regions – including the Indian state of Kerala – have achieved impressive reductions. This paper examines infant and child mortality in Andhra Pradesh (where Young Lives research is being conducted) and in Kerala, and considers the factors explaining their differential performance. Infant mortality is found to depend on biological factors, including mother’s age and birth order, and also factors related to health service provision such as vaccinations and use of antenatal services. Other factors, such as income, education or environmental factors, are not found to impact infant mortality. By contrast, child mortality is significantly determined by economic well-being, but is substantially outweighed by other factors such as maternal education and knowledge of health practices and access to safe water. The data also show gender discrimination in Andhra Pradesh, notably against girls with only female siblings, which is absent from Kerala. We conclude that raising service levels across India toward the levels found in Kerala is a necessary step toward meeting the MDGs. Success in doing so can help empower women.